2000
DOI: 10.1007/s101030050049
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Photodiagnostics and Photobleaching Studies of Cancerous Lesions using Ratio Imaging and Spectroscopic Techniques

Abstract: Topical or systemic administration of 5-aminolaevulinic acid results in biosynthesis of the photosensitiser protoporphyrin IX (PpIX) with some selectivity for malignant lesions. Excitation near 400 nm excites both intrinsic green tissue autofluorescence and red fluorescence from PpIX which may be exploited for the optical diagnosis of malignant and premalignant disease. In this work the utility of a cooled 12-bit single chip charge-coupled device (CCD) colour camera was investigated for photodiagnostic fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…Excitation of PpIX with blue light (410 nm) results in detectable fluorescence in the red region (635 nm and 700 nm) (19). The fluorescent properties of PpIX are commonly employed in photodiagnosis, aiding clinicians in diagnosis and demarcation for excision (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Excitation of PpIX with blue light (410 nm) results in detectable fluorescence in the red region (635 nm and 700 nm) (19). The fluorescent properties of PpIX are commonly employed in photodiagnosis, aiding clinicians in diagnosis and demarcation for excision (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Two types of fluorescence indicators have been reported to be valuable: autofluorescence 5,[8][9][10][11][12][13] and protoporphyrin IX (PpIX) fluorescence. 6,[14][15][16][17][18] Previous studies have shown autofluorescence to reduce with oral malignancy; 5,9,10,19,20 however, this change is not easy to discriminate by visual inspection. A study applied classification algorithms to compare various contrast features extracted from multispectral optical images and found that the ratio of red-to-green fluorescence intensity in a 405-nm excited autofluorescence image maximized the image contrast for the differentiation of neoplastic and non-neoplastic tissue.…”
Section: Introductionmentioning
confidence: 99%
“…19,23 To increase the specificity of this method, various researchers have proposed that the intensity ratio may be a better indicator of malignancy than PpIX intensity alone. Scott et al 16 and Betz et al 19 used the red-to-green fluorescence intensity ratio and employed a commercial software package, whereas Zheng et al 23 used the red-to-blue intensity ratio with a self-developed program for contrast-enhanced fluorescence image processing. Although their results show increased specificity by this approach, there is no consensus on the intensity ratio to be used, and the foundation of these methods was not clearly explained, hence rendering their reproducibility limited.…”
Section: Introductionmentioning
confidence: 99%
“…PpIX exhibits red fluorescence (peak wavelengths at 635 nm and 700 nm) when excited by blue light (wavelength 410 nm) and therefore cells accumulating PpIX can be identified (13,14). Fluorescence diagnosis in ALA-PDT can aid the identification of pre-cancerous lesions and ensure the whole lesion is properly removed during tumour excision (15,16).…”
Section: Introductionmentioning
confidence: 99%